Ports maritimes flamands, complexe portuaire liégeois et port de Bruxelles - Rapport 2007 - Claude Mathys (National Bank of Belgium, 2009)
– This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Oostend, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centres facilitating the commodity flow. This update paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels in the period 2002 - 2007, with an emphasis on 2007. Focusing on the three major variables of value added, employment and investment, the report also provides some information about social balance and the financial situation in these ports as a whole. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. [...] In terms of maritime cargo traffic, 2007 was another excellent year for all the Flemish maritime ports, driven by the expansion of world trade. Direct value added rose in all the ports in Flanders. Both maritime and non-maritime branches as a whole expanded. The ports of Antwerp and Zeebrugge enjoyed particularly high growth in direct value added of their maritime branches, unlike the ports of Ostend and Ghent where growth was higher in the non-maritime branches. Direct employment also rose, albeit in less spectacularly: the more moderate growth of the biggest Flemish port - Antwerp - set the tone for the overall result. In this favourable economic environment, investment increased in the Flemish ports as a whole, after falling in 2006. The ports of Antwerp, Ostend and Ghent recorded very high levels of investment in 2007, although not reaching Antwerp's peak of 2005. The rise was more marked in the maritime branches, especially in the ports of Antwerp and Ostende, but the non-maritime branches also recorded strong expansion. With the completion of the Albert II dock, investment in the port of Zeebrugge levelled out, even though there are some other projects in progress. The volume of cargo handled in the port of Liège again increased in 2007. Direct value added recorded strong growth and employment picked up. Both these variables improved on the previous year's figures, thanks mainly to the metalworking and energy sectors. Investment doubled. A major factor behind this increase was the construction of a new bioethanol plant in Wanze. Despite these good results, the threat of declining activity in the ArcelorMittal factories in Liège has prompted the local port to pursue its strategy of diversifying traffic. Preparatory work on the land for the Trilogiport project began at the end of 2008. The volume of cargo handled at the port of Brussels rose in 2007. Despite the restrictions on the land available for port-related activities, both value added and employment in the port of Brussels increased. There was a notable fall in investment in the non-maritime branches with the completion of the water purification plant. However, the port authority is continuing with its infrastructure renovation work. The present report provides a comprehensive account of these issues, giving details per economic sector, though the comments are confined to the main changes that occurred in 2007
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments